Fuel Tankering Practices in Aviation and Average Origin-Airport Fuel Prices: Evidence from the Brazilian Domestic Market - Tizeu, Letícia Alves; Caetano, Mauro; da Silva, Evandro José (Transportation Development Research, 2025)
Considered one of the most significant costs to aviation, the identification of strategies for aircraft fueling can contribute to optimizing air transportation resources. Therefore, this study investigates the practice of fuel tankering, addressing a theoretical gap resulting from the lack of comprehensive, network-wide route assessments of fuel tankering practices, as current evaluations are predominantly conducted on a per-flight basis. This study employs descriptive analysis combined with regression methods to examine public data from Brazilian aviation, supplied by the Brazilian National Civil Aviation Agency. The data includes details such as origin, destination, aircraft type, and flight times. Additionally, it incorporates fuel price information from the Brazilian National Petroleum Agency, comparing data from 2019—before the pandemic—and from 2022 and 2023—after the pandemic. The findings show that a R1.00 per liter increase in fuel price at the source is linked to a reduction of about 32,970 kg in the volume of refueled fuel. This suggests that fuel tankering can offer significant cost savings for airlines, especially on routes with high destination fuel prices. However, these benefits are balanced by increased CO2 emissions, highlighting a conflict between economic gains and environmental sustainability. This study recommends optimizing tankering strategies and aligning them with broader regulatory and environmental goals.